Smudge cells in peripheral blood smears did not differentiate chronic lymphocytic leukemia from other B-cell chronic lymphoprolipherative diseases - Matos,Daniel M. (2009)
Smudge cells has been classically associated with chronic lymphocytic leukemia (CLL), but they are found in peripheral blood tests for other chronic B-cell lymphoproliferative diseases (CLD). We investigated whether the percentage of smudge cells in peripheral blood smears can be used in the clinical practice to differentiate CLL from other B-cell CLD. The peripheral blood smears of 63 patients with the diagnosis of CLL and 62 with other B-cell CLD were analyzed. Three hundred cells (both lymphoid cells and smudge cells) were counted for each peripheral blood smear. A comparison of the percentage of smudge cells between the two groups was performed and, subsequently, 5 cut-off values were fixed (10%, 20%, 30%, 40% and 50% of smudge cells) with the aim of defining cases as "positive" or "negative" for smudge cells and verifying whether there are any differences between CLL and the other B-cell CLD. The percentage of smudge cells in patients with CLL (median 26%, 4%-86%) was higher than in patients with B-cell CLD (median 14%, 1%-64%). However, none of the cut-off values tested presented suitable values of sensitivity, specificity and positive predictive value to separate the two groups. As it is necessary to have a single cut-off value with high sensitivity, specificity and positive predictive value to infer the diagnosis of CLL in the clinical practice, we concluded that smudge cells are not fitting to differentiate CLL from other B-cell CLD.